Flight of the Outcast : the Academy, year 1 - Strickland, Brad (Strickland, Brad. Academy., 2010)
When thirteen-year-old Asteria's family is killed by space raiders, she leaves their farm on the fringe planet Theron and uses her desire for revenge as motivation at the Royal Military Academy, where she is treated as a second-class citizen because of her father's unfairly stained reputation.